2015
DOI: 10.15446/acag.v64n3.43087
|View full text |Cite
|
Sign up to set email alerts
|

Simbiosis de micorrizas arbusculares en plantas de arroz (Oryza sativa L.) en condiciones de inundación y secano

Abstract: En la Unidad Científico Tecnológica de Base Los Palacios, Cuba, a 22° 34’ 32.73’’ N y 83° 14’ 11.95’’ O, se evaluó el efecto de la inundación sobre la colonización de hongos micorrízicos ar-busculares durante la fase vegetativa de plantas de arroz cultivar INCA LP-5.  Se realizaron dos experimentos en condiciones de invernadero en macetas con una capacidad de 800 g de suelo, ambos experimentos en un diseño experimental completamente aleatorizado.  Uno de ellos se realizó con Rhizophagus (=Glomus) intraradices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Several Cuban authors have reported similar effects on mycorrhizal functioning, nutritional status and yields by inoculating different crops with efficient strains of AMF in different types of soils (Ruiz et al, 2012;González et al, 2015;Simó et al, 2016). Specifically, positive results have been reported for inoculation of the R. intraradices / INCAM-11 strain in different crops, such as grasses, bananas, Jackbean, cassava, rice, beans, among others, and types of soils and substrates, provided that the pH of these, in the depth of the soil in which the roots grow, is greater than seven (Rivera et al, 2015;González et al, 2016;João et al, 2016;Ruiz-Sánchez et al, 2016;Simó-González et al, 2017). The order of effectiveness of the different strains found in this work was also similar to that reported by previous authors in soils with light alkalinity conditions (pH between 7 and 8), suggesting that the strains respond differently and reproducibly to soil conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Cuban authors have reported similar effects on mycorrhizal functioning, nutritional status and yields by inoculating different crops with efficient strains of AMF in different types of soils (Ruiz et al, 2012;González et al, 2015;Simó et al, 2016). Specifically, positive results have been reported for inoculation of the R. intraradices / INCAM-11 strain in different crops, such as grasses, bananas, Jackbean, cassava, rice, beans, among others, and types of soils and substrates, provided that the pH of these, in the depth of the soil in which the roots grow, is greater than seven (Rivera et al, 2015;González et al, 2016;João et al, 2016;Ruiz-Sánchez et al, 2016;Simó-González et al, 2017). The order of effectiveness of the different strains found in this work was also similar to that reported by previous authors in soils with light alkalinity conditions (pH between 7 and 8), suggesting that the strains respond differently and reproducibly to soil conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, positive results have been obtained by the inoculation of efficient strains of arbuscular mycorrhizal fungi (AMF) in different crops and soil types in Cuba (Rivera et al, 2015). The integration of AMF in nutrient supply schemes, whether in mineral or organic-mineral fertilizers, has led to decrease in the quantities used, maintaining high yields and adequate nutritional status (Rivera et al, 2007;González et al, 2015;Ruiz-Sánchez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%